Влияние лечебно-профилактических препаратов на содержание триглицеридов в печени и сыворотке крови крыс, получавших высокожировой рацион на фоне дисбиоза и иммунодефицита - Гоженко, А.И.; Левицкий, А.П.; Левченко, Е.М.; Ткачук, В.В. (Актуальні проблеми транспортної медицини, 2014)
При моделировании у крыс иммунодефицита (с помощью цитостатика циклофосфана) и дисбиоза (с помощью линкомицина) на фоне высокожирового рациона
установлено повышение содержания триглицеридов (ТГ) в печени, а также содержания ТГ, холестерина и уровня печеночных маркеров (билирубин, АЛТ и щелочная
фосфатаза) в сыворотке крови. Введение антидисбиотических препаратов (квертулин, квертгиал и лизоцим) снижало содержание ТГ в печени, а также уровень ТГ,холестерина и печеночных маркеров в сыворотке крови. При моделюванні у щурів імунодефіциту (за допомогою цитостатика циклофосфана) і дисбіоза (за допомогою
лінкоміцина) на тлі високожирового раціону встановлено підвищення вмісту
тригліцеридів (ТГ) в печінці, а також
вмісту ТГ, холестерину і рівня печінкових
маркерів (білірубін, АЛТ і лужна фосфатаза) в сироватці крові. Введення антидисбіотичних препаратів (квертулін,
квертгіал і лізоцим) знижувало вміст ТГ
в печінці, а також рівень ТГ, холестерину
і печінкових маркерів в сироватці крові. In recent years there appeared data
about close pathogenic connection of
obesity with dysbiotic changes in organism.
As is well known, the development of
dysbiosis a large extent due to the
presence in the body of immunodeficiency.
The aim of our study was to
investigate the effect on triglyceride content
in the liver and in the blood serum of a
number of new therapeutic and
prophylactic agents with anti dysbiotic
action. Such agents including kvertulin,lysozyme in gelatin and kvertgial.
In work were used the following
materials: quercetin; inulin made of chicory
roots, calcium citrate; hyaluronic acid;
lysozyme, of which was prepared the
following drugs: In work were used the
following materials: quercetin; inulin made
of chicory roots, calcium citrate; hyaluronic
acid; lysozyme, which was prepared from
the following formulations: “Kvertulin”,
“Kvertgial”, “Lysozyme in gelatin.” In
experiments were used 35 Vistar line white
rats. Dysbiosis was induced by antibiotic
lincomycin. Immunodeficiency created by of
cytostatic intraperitoneal injection
cyclophosphamide. High fat diet (HFD) was
prepared by adding 15 % of unrefined
sunflower oil to the mixed fodder. Duration
of experiment was 21 days. Therapeutic
drugs started to to be entered from the first
day of the experiment. Mortification of of
animals was performed using thiopental
anesthesia (20 mg / kg) at day 22 by total
exsanguination from the heart. Prepared
blood serum and liver part were excised,
that was stored before the test at -30 °C.
In liver homogenate was determined
the contents of triglycerides (TG)and in
blood serum except TG were determined
cholesterol, bilirubin, ALT and alkaline
phosphatase (ALP).
In pathological liver significantly were
increased fat content, which is significantly
reduced under the influence of anti
disbiotical drugs we tested, but the greatest degree (up to norm) — under the influence
of Kvertulina. In the blood serum of rats with
triple pathology significantly increase the
content TG and cholesterol. Under the
influence of anti disbiotic drugs TG content
decreases slightly, whereas cholesterol was
significantly reduced to near normal.
Determination of hepatic markers in
blood serum (bilirubin, ALT and alkaline
phosphatase) showed a significant increase
their level, indicating the development of
hepatitis (steatohepatitis). Under the
influence of anti disbiotic drugs, such as
lysozyme and kvertulin was significantly
reduced bilirubin level and ALT (almost back
to normal), and alkaline phosphatase
activity only tends to decrease.
HFD on the background of dysbiosis
and immunodeficiency causes the
development of gepatosteatos and
steatohepatitis, which is accompanied by
hypertriglyceridemia and
hypercholesterolemia. Anti disbiotic drugs,
especially kvertulin containing hepatic
protector quercetin, prebiotic inulin and
calcium citrate has a pronounced
therapeutic and preventive action, not only
eliminating the hepatic steatosis, but also
eliminating steatohepatitis.